DIGITALISASI DAN GREEN ECONOMY TRANSFORMASI UMKM MENUJU BISNIS RAMAH LINGKUNGAN BERBASIS TEKNOLOGI: Peran Digitalisasi dalam Transformasi UMKM dan Implementasi Green Economy dalam Praktik UMKM - Sabina Ayu Gosye Nova (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2026)
The development of digital technology offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to transform into more innovative and environmentally friendly businesses. This article analyzes the role of digitalization in supporting green economy practices in MSMEs, including operational efficiency, supply chain monitoring, product innovation, and transparency in business processes. The research method used is a literature study with a descriptive-qualitative approach, based on the analysis of books, journals, articles, and documents related to digitalization and green economy. The findings indicate that digitalization acts as the main driver of MSME transformation, while implementing green economy principles enhances environmental sustainability and creates new economic opportunities. The integration of these concepts requires collaborative support from government, non-profit organizations, and communities to optimize implementation. This study provides strategic guidance for MSMEs to combine technological innovation with sustainable business practices.